Disaster response and recovery strategies and tactics for resilience - McEntire, David A. (Wiley, 2022)
"Disasters are defined as deadly, destructive, and disruptive events that occur when hazards, or multiple hazards, interact with vulnerability. The hazard can be an agent or threat such as earthquakes, hurricanes, tsunamis, industrial explosions, or terrorist's attacks. Vulnerability, on the other hand, refers to the proneness of people to disasters based on factors such as their geographic location, exposed property, and level of income. The disaster response is the activity in the immediate aftermath of a disaster to protect life and property. Disaster recovery is the process, policies and procedures that are related to returning the affected community to pre-disaster or preferably, improved conditions."